Towards a More Effective Individual Learning Account Program in Indonesia: Policy Insights from South Korea’s Tomorrow Learning Card - Fajarsyah, Reza; Okfernando, Raphel; Ridwan, M. Alfie; Ayuningtyas, Maeshita Fariska (UI Scholars Hub, 2025)
Indonesia has implemented the Individual Learning Account system under the name Kartu Prakerja, or Pre-Employment Card, to support workforce development. This study examines its effectiveness by comparing it with South Korea’s Naeil Baeum Card (Tomorrow Learning Card). Despite its role in improving skills, Indonesia’s Individual Learning Account system faces challenges in funding sustainability, eligibility control, participant engagement, and training relevance. Additionally, financial support is provided at a fixed amount, regardless of training type. Using comparative policy and fishbone analysis, this study identifies key differences and best practices from South Korea. The findings highlight that South Korea’s co-funding model, employer contributions, and flexible training mechanisms create a more sustainable system. In contrast, Indonesia’s government-funded model faces financial constraints. This study recommends funding diversification, enhanced eligibility verification, an income-based co-payment system, training-specific financial support, and improved fund validity to enhance Indonesia’s Individual Learning Account system.